Towards Developing a MAC protocol for outer-WBAN communication for pilgrims’ health monitoring during hajj: A feasibility study - Murtaza Rashid Al. Masud, Shah; Abu Bakar, Asmidar; Yussof, Salman (International Journal of Engineering and Technology, 2018)
Due to lack of deployment of information and communication technology (ICT) for real-time pilgrims’ health monitoring during Hajj, many pilgrims left untreated, get lost and suffer from severe health problems which sometimes end with injury, traum and even death. WBAN is an emergent healthcare technology and can be deployed at Hajj ritual sites for pilgrims’ health monitoring. WBANs body coordinator or gateway as an aggregator collect data from body nodes or sensors, store them and then forward to the healthcare stations for analyzing the data through outer-WBAN communications. Currently, most of the existing research works focused on intra-WBAN communications while the technical issues, problems, opportunities and standard correlated to outer-WBAN are not well discussed and mentioned. Since, medium access control (MAC) protocol is responsible for channel access, lower delay, and energy efficient transmission of data packets. Therefore, designing of an efficient and reliable MAC protocol is the earnest research demand to alleviate the aforementioned obstacle. In this research, a feasibility study has been completed to identify the problem and a proposal has been made to develop a suitable MAC protocol for outer-WBAN communication for pilgrims’ health monitoring during Hajj.